Pengaruh Pemberian Biourin Sapi dan Lama Inkubasi Terhadap Ketersediaan Hara Nitrogen dan Fosfor pada Tanah Podsolik - Nadya Nabila Rahma; Abdul Haris; Abdul Hadi (Acta Solum, 2023)
Podzolic soil is characterized by acidic condition, low base saturation, and low CEC and nutrient contents. The use of chemical fertilizers in agriculture may damages soil and environment and may eventually affect the health of humans. The objective of this study was to quantify the effect of cow urine on changes in pH, available N (NH4+ and NO3-), and available P of Podsolic soil. This study employed the completely randomized design two factors, in which first factor was the amounts of applied cow biourine: control (without biourine, 5.2, 10.4 and 15.6 mL of biourine), while the second factor was the incubation period: 2 and 4 weeks. Following the completion of each incubation period, soil pH, contents of ammonium, nitrate, and available phosphrous were determined for each treatment. Results of this study showed that the application of cow biourine with an incubation time of two and four weeks significantly influenced the ammonium and nitrate contents in soil. The higher amount of biourine applied, the higher ammonium and nitrate contents in the soil. The research results also showed that the application of cow biourine had an influence on available P content, but had no effect on changes in soil pH.